2021
DOI: 10.48550/arxiv.2112.04456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Pantheon+ Analysis: Forward-Modeling the Dust and Intrinsic Colour Distributions of Type Ia Supernovae, and Quantifying their Impact on Cosmological Inferences

Abstract: Recent studies have shown that the observed colour distributions of Type Ia SNe (SNIa) are welldescribed by a combination of distributions from dust and intrinsic colour. Here we present a new forward-modeling fitting method (Dust2Dust) to measure the parent dust and colour distributions, including their dependence on host-galaxy mass. At each fit step, the SNIa selection efficiency is determined from a large simulated sample that is re-weighted to reflect the proposed distributions. We use five separate metri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 31 publications
4
32
1
Order By: Relevance
“…With this mind, it is natural to suspect that the colour correction in this case is predominantly driven by dust extinction. This picture is consistent with the probabilistic model of SN colours used by Popovic et al (2021) for which the red tail of the observed colour distribution arises entirely from reddening due to dust. Following this interpretation, we conclude that a low, nearly Planckian value of the Hubble constant (or a longer distance scale) obtained in our analysis for c ref ∼ < −0.1 results most likely from a stronger dust extinction and thus higher intrinsic brightness (∆m ≈ 0.17 for c ref = −0.13 and model B) of SNe in the calibration sample than in the baseline model.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…With this mind, it is natural to suspect that the colour correction in this case is predominantly driven by dust extinction. This picture is consistent with the probabilistic model of SN colours used by Popovic et al (2021) for which the red tail of the observed colour distribution arises entirely from reddening due to dust. Following this interpretation, we conclude that a low, nearly Planckian value of the Hubble constant (or a longer distance scale) obtained in our analysis for c ref ∼ < −0.1 results most likely from a stronger dust extinction and thus higher intrinsic brightness (∆m ≈ 0.17 for c ref = −0.13 and model B) of SNe in the calibration sample than in the baseline model.…”
Section: Discussionsupporting
confidence: 88%
“…The reference colours required to obtain the Planck value of the Hubble constant coincide with the blue end of the observed colour distribution in the cosmological and calibration sample. Interestingly, the reference colour for the preferred model B is within the 1σ range of the intrinsic colour distribution derived from the Pantheon+ SN sample (Popovic et al 2021).…”
Section: Hubble Constantsupporting
confidence: 62%
See 1 more Smart Citation
“…A brief overview of SNANA is as follows: 1) fluxes are generated from a source model, with noise and detection characterized in survey-specific methods alongside a rest-frame SED for each epoch that is subject to cosmological and galactic effects, 2) the SED is integrated for each filter to obtain broadband fluxes, which are further subjected to surveyspecific measurement noise, and 3) candidate logic and spectroscopic identification efficiencies are applied. For this paper, we take our Pan-theon+ simulation inputs from Brout et al (2022), a brief overview of which is presented in Table 2 of Popovic et al (2021a).…”
Section: Simulationsmentioning
confidence: 99%
“…Type Ia supernovae (SNe Ia) were used to discover the acceleration of the universe (Riess et al 1998;Perlmutter et al 1999), and are now being used to make some of the most precise measurements of the equation-of-state of dark energy (𝑤, e.g., Garnavich et al 1998;Suzuki et al 2012;Betoule et al 2014;Scolnic et al 2018;DES Collaboration et al 2019;Brout et al 2022) and the current expansion rate parameterized by H 0 (e.g., Freedman et al 2019;Riess et al 2021). However, recent analyses have shown that improvement of these measurements depends on a better understanding of the impact of dust around SNe Ia and how it relates to the scatter found in standardized SNe Ia brightnesses Popovic et al 2021a).…”
Section: Introductionmentioning
confidence: 99%